Résister à l'exploitation : une histoire de l'opposition péruvienne aux transnationales minières de 1901 à nos jours - Lamarche, Steve (Université de Montréal, 2014)
Throughout the twentieth century, the Peruvian mining industry has undergone a series of transformations that have had profound economical, social and political impact on the nation and its citizens. These changes, however, were not without opposition. In fact, studying recent Peruvian history from a resistance point of view, three different periods come to the foreground. From 1901 to 1930, workers were mostly Andean peasants coerced to work in mines by means of a debt-peonage system called enganche. Their means of resistance, having no union at this time, were mostly individual and short-termed, such as leaving their workplace without completing their contract. One non-governmental organization (NGO) concerned about miners' working conditions was the Asociación Pro-Indígena, composed of progressive Peruvian intellectuals such as Dora Mayer, who studied the practice and impact of the enganche system. The second – spanning from 1930 to 1980 – is both the longest and most important period for studying the transformation of the mining industry and its impact. It is during this period that unions were created and expanded, despite facing serious state oppression. In 1969, the Federación Nacional de los Trabajadores Mineros y Metalúrgicos del Perú (FNTMMP) was created and was the first successful attempt to unite all mining industry workers into one organization. This federation was a prominent actor in the social movement of the seventies, and was one of the organizations that contributed to General Bermúdez's resignation and the presidential elections of 1980 which signaled Peru’s return to democracy after over a decade of military rule. Parallel to this return to representative democracy was the launching of Sendero Luminoso's armed struggle, and the subsequent civil war. This period affected greatly unions of all sectors, who were caught between Sendero Luminoso's purges and the Army's repression. The third period begins with Alberto Fujimori's presidential election in 1990. This president is known for his victory against Sendero Luminoso and the neoliberal reforms he pushed forward by way of quasi-authoritarian practices (such as the suspension of congress in 1992). These reforms mainly consisted in the government changing legislation in order to help foreign companies, such as mining firms, to benefit from Peru's primary resources. Resisting this new paradigm are the communities organized through the Confederación Nacional de las Comunidades Afectadas por la Minería (CONACAMI). Finally, although each period demonstrates distinct means to battle against transnational mining companies and to circumscribe and seek repair for abuses committed, there is a continuity across them: the subalterns' will to be heard.
Keywords: Histoire du Pérou; History - Latin American / Histoire - Latino-américaine (UMI : 0336); Industrie minière; Labor movement; Luttes sociales; Mining industry; Peruvian history; Social conflicts; Syndicalisme; Twentieth century; Vingtième siècle